Pemanfaatan Tanaman Herbal sebagai Alternatif dalam Pengobatan Hipertensi di Desa Mersam Kabupaten Batang Hari - Agung As’adi, M.Henityo; Nabhaki, Firelza; Ripani, Izani Fathya; Arista, Dina; Susanti, Siti Melvy; Lestari, Wiwik; Wahyuni, Intan Sri; Sandy, Sapna Ari; Hayeti, Triana Najma; Prianggie, Sherly Alensia (Jurnal Abdimas Kesehatan (JAK), 2025)
One type of community service is Real Work Lectures (KKN), which aims to apply knowledge and skills in social life. In Mersam Village, Mersam District, Batanghari Regency, Jambi, there is a real work program with the theme "Community Movement for Health Care, Response to Safe Use of Medicines and Cosmetics." The aim of this campaign is to increase public awareness about healthy lifestyles, appropriate use of medication, and choosing safe cosmetics. Initial surveys, health education, junior pharmacist courses, and pharmaceutical product expos are the methods used in this activity. The results show that the public understands better the correct use of medicines, the use of herbal plants, and checking the safety of cosmetics through BPOM. Utilization of digital media as a method of continuing education and collaboration with health workers can support program sustainability.